2017
DOI: 10.1016/j.micres.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of free-Living nitrogen fixing Streptomyces in soils of the badlands of South Dakota

Abstract: Biological Nitrogen Fixation is critical for ecosystem productivity. Select members of Bacteria and Archaea express a nitrogenase enzyme complex that reduces atmospheric nitrogen to ammonia. Several nitrogen fixing bacteria form symbiotic associations with plants, but free-living diazotrophs also contribute a substantial amount of nitrogen to ecosystems. The aim of this study was to isolate and characterize free-living diazotrophs in arid lands of South Dakota Badlands. Samples were obtained from sod tables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 59 publications
1
45
0
1
Order By: Relevance
“…Alam et al (2012) achieved an increase in yield (11%) of geranium herbs inoculated with Streptomyces sp. The ability of some Streptomyces to fix nitrogen as free-Living is an additional advantage in offsetting nitrogen losses from soil (Dahal et al, 2017). It has been documented that Actinobacteria promotes legume symbioses through hyphal elongation for symbiotic fungi (Schrey and Tarkka, 2008) and /or by increasing nodulation for nitrogen fixing symbiosis (Sathya et al, 2017).…”
Section: Box 2 | Features and Taxonomy Of Actinobacteriamentioning
confidence: 99%
“…Alam et al (2012) achieved an increase in yield (11%) of geranium herbs inoculated with Streptomyces sp. The ability of some Streptomyces to fix nitrogen as free-Living is an additional advantage in offsetting nitrogen losses from soil (Dahal et al, 2017). It has been documented that Actinobacteria promotes legume symbioses through hyphal elongation for symbiotic fungi (Schrey and Tarkka, 2008) and /or by increasing nodulation for nitrogen fixing symbiosis (Sathya et al, 2017).…”
Section: Box 2 | Features and Taxonomy Of Actinobacteriamentioning
confidence: 99%
“…However, recently, serendipity led to the finding of five nitrogen-fixing Streptomyces. The strains yielded nifH products that aligned with those of Scytonema, Nostoc, and Bradyrhizobium [126]. However, the nitrogen-fixing activity remains to be studied further in Streptomyces.…”
Section: Pgp Streptomyces Against Abiotic Stressorsmentioning
confidence: 94%
“…The different systems are similar in their nitrogen fixing mechanism and sensitivity to oxygen. However, they differ in their metal content and encoding genes; nifH being the most studied and conserved nitrogenase enzyme complex-encoding gene [126]. Only Streptomyces thermoautotrophicus was once believed to fix atmospheric nitrogen; however, MacKellar et al [127] demonstrated its lacking nitrogen-fixing ability.…”
Section: Pgp Streptomyces Against Abiotic Stressorsmentioning
confidence: 99%
“…Siguiendo la técnica del fenol hipoclorito de Lara et al (2007) se detectó una concentración de 0,63 mg/L de amonio en el medio de cultivo de Streptomyces cirratus (ST3E). De acuerdo con Dahal et al (2017) no se conocen Streptomyces fijadores de nitrógeno, es por ello que proponemos a Streptomyces cirratus (ST3E) como candidato para profundizar mayores estudios y confirmar la presencia de los genes nif y sus posibles mecanismos para poder fijar el nitrógeno atmosférico.…”
Section: Identificación De Las Actinobacterias Aisladas Por Secuenciaunclassified